The Relationship Between Teachers’ Body Image Perception and Eating Habits - ALTINBAŞ , Eren; ÜNVEREN , Alparslan (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2024)
The correlation between educators’ eating habits and body image is a topic of interest for numerous researchers and educators. This study examined teachers’ body perceptions and eating attitudes concerning individual variables and explored the relationship between these concepts. The study employed a quantitative research design and involved 279 teachers selected through convenience sampling. Alongside the personal information form, the study employed the Eating Attitude Test and the Body Perception Scale as instruments for data collection. The study employed an independent samples t-test to analyze teachers’ eating attitudes and body perceptions concerning individual variables, while Pearson correlation analysis was utilized to explore the relationship between concepts. Results: Although body perception and eating attitudes among participants do not vary by gender or marital status, individuals who engage in regular physical activity exhibit significantly enhanced body perception. Furthermore, there exists no statistically significant correlation between the participants’ eating attitudes and body perception. The results indicate that teachers’ dietary habits do not significantly influence their body perception. Nevertheless, it is imperative to recognize that these findings, in isolation, are inadequate and require contextualization within a wider framework.